A randomised controlled intervention trial evaluating the efficacy of an Australianised Mediterranean diet compared to the habitual Australian diet on cognitive function, psychological wellbeing and cardiovascular health in healthy older adults (MedLey study): protocol paper. Issue 1 (December 2015) - Davis, Courtney; Bryan, Janet; Hodgson, Jonathan; Wilson, Carlene; Dhillon, Varinderpal; Murphy, Karen
Abstract Background The Mediterranean diet (MedDiet) is associated with considerable health benefits for cardiovascular and cognitive health, particularly within the Mediterranean basin. Whether Australian populations will similarly benefit from the MedDiet is unknown. We aim to assess the effects of a MedDiet on cognitive and cardiovascular health indicators amongst the elderly (MedLey study). Here we describe in detail the protocol for the MedLey study. Methods Medley is a randomised, parallel controlled dietary intervention trial. Data collection occurred at the Sansom Institute for Health Research, University of South Australia, Adelaide, South Australia, Australia between 2013 and 2015. Omnivorous men and women aged ≥65 years, who were non-smokers, had no previously diagnosed cardiovascular disease, history of brain trauma, cognitive impairment, major disease or cancer were recruited from the general public (n  = 166). The intervention comprised an Australianised version of the traditional MedDiet characterised by small amounts of red meat, processed deli meats and high sugar foods; moderate amounts of dairy and poultry; and a high plant food content including abundant extra virgin olive oil. Volunteers were stratified by age, gender and body mass index (kg/m2 ) to follow either their habitual diet (control condition) or the intervention MedDiet for 24 weeks. Primary outcome measures included cognitive function, endothelial function, cerebrovascular flow, blood lipids, inflammatory markers, fasting glucose and insulin, blood pressure, and body composition. Secondary outcomes included food cravings, psychological wellbeing and DNA damage markers. These were assessed at baseline, 12 and 24 weeks. Dietary intakes were assessed at baseline, two and four months to assess adherence to the prescribed diet. For main outcome measures, groups will be compared over time using a linear mixed effects model, with Cohen's d effect sizes. Subgroup analysis based on adherence to the intervention, medications and alcohol consumption may be performed in an exploratory fashion. Discussion The MedLey study will provide evidence as to whether dietary changes in line with an Australianised MedDiet can benefit cognitive performance, endothelial function and other cardiovascular risk factors and psychological wellbeing amongst older Australians. Results could inform formation of national dietary guidelines and nutrition-related practices such as dietetics. Trial registration The trial was registered on the Australia New Zealand. Clinical Trials Register (ACTRN12613000602729 ). Trial registration date: 27 May 2013.